Specific progesterone binding to a membrane protein and related nongenomic effects on Ca2+-fluxes in sperm - Falkenstein, Elisabeth; Heck, Marina; Gerdes, Dirk; Grube, Daniel; Christ, Michael; Weigel, Michael; Buddhikot, Madhavee; Meizel, Stanley; Wehling, Martin (Endocrinology, 1999)
Rapid, nongenomic effects of steroids are supposed to be transmitted by membrane receptors unrelated to the classic intracellular steroid receptors. In this context, a putative progesterone membrane binding protein (mPR) has been identified, recently. Here we show that expression of mPR-cDNA in CHO cells leads to increased microsomal progesterone binding. This result is mirrored by effects of an antibody raised against the recombinant E. coli mPR which suppressed the rapid progesterone-initiated Ca2+ increase in sperm. Our results support the assumption that mPR represents the first steroid membrane receptor or a part of it involved in rapid, nongenomic steroid signalling.